(untitled) (Research, Society and Development, 2024)
The rehabilitation of atrophic maxillas is a challenge in dentistry due to the anatomical complexity and the need for durable restorations. The All-on-Four technique, developed by Dr. Paulo Malo, is an innovative approach that uses four strategically placed dental implants to support a complete fixed prosthesis, maximizing the use of available bone and minimizing bone grafts. Studies show high success rates and patient satisfaction, improving masticatory function and quality of life, as well as offering economic advantages and lower postoperative morbidity. Despite positive results, the technique faces challenges such as bone density assessment, patient selection, implant longevity, and peri-implant health maintenance. Thus, this narrative literature review aims to analyze publications regarding the rehabilitation of atrophic maxillas using the All-on-Four technique.